APPROXIMATE CALCULATION OF THE CIRCULAR SOIL CUTTING CAPACITY - V. A. Nikolayev (Вестник СибАДИ, 2019)
Introduction. Rotary cultivators are necessary for circular soil cutting while forming the underlayment and slopes of highways. Therefore, the objective of the research is a theoretical substantiation of constructive and sensitive parameters for the rotary ripper. The researchers usually use synthesis method to evaluate theoretical evaluation of the energy consumption on the development of soil. The researchers also carry out an indicative calculation of basic design parameters and power drive of rotary ripper.Materials and methods. The author developed a methodology for calculating the indicative rotor power. Moreover, the author detected changes of the effective frontal sections of the working body in the process of the rotor circulation by means of the length measuring of a frontal section.Results. As a result, the author defined rational working parameters of circular cutting ground and calculated the angular velocity of the active working body. Moreover, the author also identified the required average torque and approximate rotor power.Discussion and conclusions. A simple and intuitive method based on accepted formulas of strength of materials, theoretical mechanics and other sciences is required for practical calculations of the working vehicles’ bodies. The author finds out that on the basis of the synthesis method the assessing energy expenditure on the development of soil may be defined, the analysis of the interaction with soil working bodies can be made.